Policing, Recognition, and the Bind of Legal Cynicism. (3rd June 2020) - Campeau, Holly; Levi, Ron; Foglesong, Todd
Abstract: We draw on a unique dataset of 60 semi-structured interviews with recently arrested suspects in Cleveland, Ohio, a city currently under federal consent decree due to police use of excessive force. Through these interviews we shed light on an apparent paradox in research to date—that residents of disadvantaged communities are deeply skeptical about policing, while still believing that the police remain a viable institution for seeking security in their communities. By connecting research on legal cynicism with insights from cultural sociology and the sociology of law, we find that respondents make meaning of this apparent paradox – and the resulting bind in which they find themselves – by stressing the promise of law that underwrites a transformative potential of policing. Through these ideals of legality, residents aspire to material and symbolic forms of recognition from law enforcement, ranging from police presence and safety, to expressions of understanding and feelings of worth. We propose that this desire for broad recognition is central to how suspects make sense of their reliance on police, and we suggest further research into how this struggle for recognition provides a cultural approach for understanding social inequality and its intersection with legality and criminal justice.